The Men’s Group at St. Pius V: A Case Study of a Parish-Based Voluntary Partner Abuse Intervention Program - Maxine Davis PhD, MSW, MBA; Melissa Jonson-Reid PhD, MSW; Charles Dahm O.P., PhD; Bruno Fernandez MSW; Charles Stoops PhD, MSW; Bushra Sabri PhD, MSW (American Journal of Men's Health, 2020)
Literature on Latino men and intervention for intimate partner violence/abuse (IPV/A) is slim. Over 100 men have voluntarily sought help for IPV/A perpetration from “The Men’s Group” (TMG) at St. Pius V parish in Chicago, IL (US) and remained engaged for extended periods. Given the rarity of prolonged non-court mandated engagement in batterer intervention programs (BIPs), a case study was conducted to explore how TMG functions. Drawing on multiple data sources, this study examined development and implementation of TMG, while also investigating contextual factors, motivators and facilitators of participants’ involvement. Data revealed that TMG functions within a supportive community context by using a mixture of traditional techniques and innovative practices, creating a unique treatment modality. The program was found to be culturally-sensitive and spirituality-based. Reasons for initial attendance varied but included: (1) fear of losing or actual loss of their partner/family; (2) acknowledging a problem and desiring to change for self or others; and (3) a desire to reach inner peace. Three themes shed light on why men remain engaged in TMG, including: (1) being met with respect by facilitators; (2) experiencing TMG as “family”; and (3) gaining benefits. Reliance upon the criminal justice system is not enough to address IPV/A perpetration. This program shows promise as an alternative or supplement to traditional BIPs, which typically rely on clients being court-mandated to attend treatment. Given the widespread nature of IPV/A, understanding the operation of potential community-based alternatives or supplements to BIPs is critical in widening access to treatment.